PERAN BUDAYA ORGANISASI DALAM MENDUKUNG KEBERHASILAN IMPLEMENTASI KNOWLEDGE MANAGEMENT SYSTEMS - Christin . (Bina Ekonomi, 2006)
The rapid change of business environment has made -organizational knowledge as something crucial. The use of information technology as a media in transferring and distributing knowledge in an organization has become more common and wide spread. One of the strategies to improve the access to the requirement of real-time and reliable information is through development of knowledge management system (KMS). However, supporting sophisticated information technology is not guarantee to the successful of KMS implementation. The development of supporting organizational culture could be the key factor to achieve effective Knowledge Management (KM).